The Heavy metals contamination and health risk assessment in food samples from the Democratic Republic of the Congo: A systematic review - Lievins-Corneille Mputu Malolo; Jocelyn Mankulu Kakumba; Patrick Ndelo Matondo; Yannick Nuapia Belo; Josaphat Ndelo- (Orapuh, Inc., 2024)
Heavy metal contamination in food poses significant risks to food safety and human health. Chronic exposure can lead to serious health issues, with the impact of contaminated foods influenced by factors such as exposure level, body mass, age, and gender. Vulnerable populations, including pregnant women and children, are particularly at risk. Long-term exposure to heavy metals is associated with various disorders, including metabolic diseases like diabetes and obesity, as well as reproductive system disruptions and cancers. This review synthesizes available data on heavy metal contamination in foods within the Democratic Republic of the Congo (DRC) and provides recommendations for enhancing heavy metal risk assessment. A comprehensive search of PubMed/MedLine, Google Scholar, ScienceDirect, and EMBASE yielded ten relevant studies published between 2011 and 2021. The distribution of studies included five from Kinshasa (50%), three from Katanga (30%), and two from Kongo Central (20%). Seventy percent of the studies focused on vegetable samples, with additional analyses of fish (30%), beef (10%), and aquatic invertebrates (10%). Risk assessment metrics, including Estimated Daily Intake (EDI), Target Hazard Quotient (THQ), Metal Pollution Index (MPI), and Hazard Index (HI), were employed in five studies (50%). The findings highlight the urgent need for comprehensive monitoring of heavy metals in diverse food sources throughout the DRC to accurately assess associated health risks and inform public health interventions.